Salen Mn Complexes Mitigate Radiation Injury in Normal Tissues - A. Rosenthal, Rosalind; Fish, Brian; P. Hill, Richard; D. Huffman, Karl; Lazarova, Zelmira; Mahmood, Javed; Medhora, Meetha; Molthen, Robert; E. Moulder, John; T. Sonis, Stephen; J. Tofilon, Philip; R. Doctrow, Susan (Anti-Cancer Agents in Medicinal Chemistry, 2011)
Salen Mn complexes, including EUK-134, EUK-189 and a newer cyclized analog EUK-207, are synthetic SOD/catalase mimetics that have beneficial effects in many models of oxidative stress. As oxidative stress is implicated in some forms of delayed radiation injury, we are investigating whether these compounds can mitigate injury to normal tissues caused by ionizing radiation. This review describes some of this research, focusing on several tissues of therapeutic interest, namely kidney, lung, skin, and oral mucosa. These studies have demonstrated suppression of delayed radiation injury in animals treated with EUK-189 and/or EUK-207. While an antioxidant mechanism of action is postulated, it is likely that the mechanisms of radiation mitigation by these compounds in vivo are complex and may differ in the various target tissues. Indicators of oxidative stress are increased in lung and skin radiation injury models, and suppressed by salen Mn complexes. The role of oxidative stress in the renal injury model is unclear, though EUK-207 does mitigate. In certain experimental models, salen Mn complexes have shown “mito-protective” properties, that is, attenuating mitochondrial injury. Consistent with this, EUK-134 suppresses effects of ionizing radiation on mitochondrial function in rat astrocyte cultures. In summary, salen Mn complexes could be useful to mitigate delayed radiation injury to normal tissues following radiation therapy, accidental exposure, or radiological terrorism. Optimization of their mode of delivery and other key pharmaceutical properties, and increasing understanding of their mechanism(s) of action as radiation mitigators, are key issues for future study.
Keywords: catalytic antioxidant